(untitled) (GAIMS Journal of Medical Sciences, 2026)
Background: Diarrhoea remains a leading cause of morbidity and mortality among children under five in India, despite the availability of simple, cost-effective preventive and management interventions such as oral rehydration solution (ORS), zinc, safe water, hygiene, and vaccination. A persistent gap between caregiver knowledge and actual practice continues to sustain the disease burden. This study aimed to assess the knowledge, attitudes, and practices regarding the prevention and control of diarrhoea among caregivers in a rural community. Methods: A community-based cross-sectional study was conducted among caregivers in the rural field practice area of a medical college in western india, using a pretested, structured questionnaire administered through household interviews. Results: A total of 437 participants were included in the study. Most respondents had heard of diarrhoea (84%) and were aware of ORS (73%), while awareness of the rotavirus vaccine was low (27%). Favorable attitudes were seen for hand hygiene (85%) and trust in health workers (74%). However, only 38% always administered ORS and 43% continued breastfeeding during diarrhoeal episodes, and only 30% consistently reheated leftover food. Overall, 73% of respondents had good knowledge and 68% had favorable attitudes, but only 18% demonstrated good practices. 27% of households reported a diarrhoeal episode in a child in the preceding six months. Conclusion: Caregivers in the study population had satisfactory knowledge and attitudes regarding diarrhoea prevention, but this was not matched by adequate preventive and management practices, reflecting a substantial knowledge-practice gap. Strengthening ORS use, continued breastfeeding during illness, and safe food-handling practices through community health worker-led counselling could help translate existing awareness into effective action.